SOSIALISASI DAN PELATIHAN PEMBUATAN PAKAN TERNAK FERMENTASI DI KELURAHAN POEA KABUPATEN BOMBANA - Asrianti, Asrianti; Hatma, Shabriyani; Nakkir, Muh.; Musrina, Musrina; Sharah, Muh. Agus; Maida, Fadliyah Al; Alamsyah, Muhammad; Astika, Andi Juni (Community Development Journal : Jurnal Pengabdian Masyarakat, 2024)
Poea Village in Bombana Regency is one of the areas that has abundant potential in agriculture and animal husbandry. Agricultural waste in the form of rice straw tends to be discarded and burned even though it can be used as animal feed. Potential in the field of animal husbandry with many people raising cattle. The problems that occur in this region are the difficulty of cattle feed, especially in the dry season and the way of raising livestock that is not managed properly. Ranchers tend to allow livestock to search for forage on their own which can disturb public order. This stage of community service activities includes village surveys, making animal feed with certain formulas consisting of rice straw, molasses, EM-4, water, salt and bran fermented anaerobically for 21 days and testing livestock. The results obtained by the F1 formula are not liked by livestock while the F2 formula of fermented feed is favored and consumed by cattle. From the feed formula test that shows optimal results, it is then disseminated to the community through training in making animal feed. The output of this activity was obtained that the general community does not know how to process agricultural waste materials into fermented animal feed which can be additional feed or alternative feed in the dry season. The purpose of this community service is to educate the farming community and ranchers to implement a better livestock system by providing feed or cages so that problems in Poea Village can be resolved.